Alta ocorrência de infecção por Mycoplasma suis em suínos de criações não tecnificadas de Mossoró, estado do Rio Grande do Norte, Nordeste brasileiro - Toledo, Mariana Aparecida [UNESP]; Leite, Alexandro Iris; Gonçalves, Luiz Ricardo [UNESP]; de Sousa, Keyla Carstens Marques [UNESP]; do Amaral, Renan Bressianini [UNESP]; da Silva, Glaucenyra Cecília Pinheiro [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2016)
Mycoplasma suis, the etiological agent of swine hemoplasmosis, has been neglected in swine herds around the world. Swine hemoplasmosis is frequently associated with hemolytic anemia, disgalacty, infertility and immunosuppression, and it results in significant economic losses. This study investigates the occurrence of M. suis in non-technified swine herds in the northeastern region of Brazil using quantitative PCR (qPCR) based on the 16S rRNA gene. Between March and August 2013, blood samples from 147 swine were collected during slaughter in the city of Mossoró, state of Rio Grande do Norte, northeastern Brazil. One hundred and twelve samples (76.19%) were positive for M. suis by qPCR assays. The range of Cqs and quantification (copies of a M. suis-16S rRNAl gene fragment/μL) was 20.86-37.89 and 1.64×101-6.64×107, respectively. One can conclude that M. suis infection have high occurrence (76,19%) in non‑technified swine-rearing systems in Mossoró in the state of Rio Grande do Norte, Brazil.
High occurrence of Mycoplasma suis infection in swine herds from non-technified farms in Mossoró, state of Rio Grande do Norte, Northeastern Brazil
Keywords: Brazil; Hemotropic mycoplasmas; Swine hemoplasmosis; Swines